Hubungan Antara Status Gizi Dan Kebiasaan Berolahraga Dengan Nilai Volume Oksigen Maksimal (VO2 Max) Pada Siswa Laki - Laki SMP Negeri Di Temanggung Selama Pandemi Covid-19 - Irvan Dwi Cahyono; Tri Agustina; Sri Wahyu Basuki; Budi Hernawan (Universitas Muhammadiyah Purwokerto, 2021)
The negative impacts of the Covid-19 pandemic include anxiety, stress, reduced appetite, boredom, and physical fitnessproblems. These conditions certainly affect the nutritional status and also the cardiorespiratory fitness of a person. InIndonesia, at least 15 out of 1000 people, or around 2,784,064 individuals suffer from heart disease. In Central JavaProvince, 0.61% of them are children aged 5-14 years old (Riskesdas, 2018). The VO2 Max value is a method formeasuring cardio respiration that can be used to determine which children are at risk of suffering from cardiovasculardisease. The VO2 Max value is influenced by several factors, including nutritional status and exercise habits. Thisstudy aimed to find out the correlation between nutritional status and exercise habits and the value of maximum oxygenvolume (VO2 Max) in male students at SMP Negeri in Temanggung during the Covid-19 pandemic. This was adescriptive-analytic study with across-sectional design. The sampling was done using the purposive sampling methodon 57 samples at SMP Negeri 1 Kaloran. It used Chi-square test for nutritional status variable with p value = 0.000 andexercise habits with p value = 0.001. The logistic regression test was used for each p-value with the nutritional statusOR value of 6.640 and the exercise habit OR value of 4.807 and with R Square value of 0.38 or 38%. There was acorrelation between nutritional status and exercise habits and the value of maximum oxygen volume (VO2 Max) inmale students at SMP Negeri in Temanggung during the Covid-19 pandemic.